Comparative analysis of antioxidant activity and content of (poly)phenolic compounds in cabernet sauvignon and merlot wines of Slovenian and Serbian vineyards - Elvira Mavric-Scholze; Dušica Simijonović; Edina Avdović; Dejan Milenković; Sabina Šaćirović; Andrija Ćirić; Zoran Marković (Food Chemistry: X)
The individual (poly)phenols of red wines cultivated in two different Western Balkan wine-growing regions were determined using the HPLC method, while the ABTS and DPPH tests were employed to investigate antioxidant activity. The reduction potential of antioxidants was determined by FRAP assay. Five distinct classes of phenolic compounds, including phenolic acids, flavan-3-ols, flavonols, stilbenes, and anthocyanins, were identified. The analyzed wines showed very good antioxidant properties. All of the studied wines exhibited a very strong correlation between their antioxidant potential and the concentration of significant antioxidants. Phenolic components that were the most represented in the investigated samples were selected for the theoretical investigation of the antioxidant effect. For this purpose, epicatechin gallate and sinapic acid were used. Their concentrations in the tested samples ranged up to 132.76 mg/mL and 125.66 mg/mL. Theoretical aspects of reactions of the mentioned compounds towards DPPH and ABTS radicals were examined.